A Video Game Using Procedural Animation - Andersson, Johan; Bergman, Lage; Hildinge, Erik; Iversen, Johan; Johansson, Daniel (My University, 2017)
Video games are played more often and by more people every year. As the consumption rises, so does the expectations on the animations. In this report, the potential of procedural animation is investigated through comparisons of different techniques within the field. These techniques include, but are not limited to, PID-controllers, genetic algorithms and contact invariant optimization. Different methods to balance, walk, fight and destroy objects are compared. The end result is a fighting game where two controllable characters face off against each other in an arena where parts of the environment are destructible.
Keywords: Data- och informationsvetenskap; Computer and Information Science